Cytotaxonomy of two species of genus Chrysolaena H. Robinson, 1988 (Vernonieae, Asteraceae) from Northeast Paraguay - Pico, Gisela M. Via Do (Pensoft Publishers, 2014)
Abstract. Chromosome counts and karyotypes of two species of Chrysolaena H. Robinson 1988 are presented in this paper. Mitotic analysis revealed that both taxa have x=10, a basic chromosome number considered characteristic of the genus. The chromosome number and the karyotype of Chrysolaena cristobaliana are reported for the first time, as well as a new cytotype and the karyotype of Chrysolaena sceptrum. Chrysolaena cristobaliana showed heptaploid cytotype with 2n=7x=70 and a karyotype composed of 46 m + 24 sm chromosomes. On the other hand, Chrysolaena sceptrum presented tetraploid cytotype with 2n=4x=40 and a karyotype with 30 m + 10 sm chromosomes. Accessory chromosomes were observed in cells of both species. The chromosome analysis showed that these species differ in the chromosome number and the total chromosome length, although they showed similar chromosome morphology and asymmetry indexes. The results support the use of chromosome data in taxonomic treatments of the American members of the tribe Vernonieae.